Examining Academic Functioning in Young Women with ADHD: How Do Girls Diagnosed in Childhood Fare Across Development? - VanPutten, Maya Miriam (eScholarship, University of California, 2010)
This investigation examined measures of academic functioning in one hundred eighty young women between the ages of 17 and 22. Data were drawn from an ongoing, 10-year longitudinal study of girls with attention- deficit/ hyperactivity disorder (ADHD), originally diagnosed in childhood, using the all-female dataset of Hinshaw (2002) and Hinshaw, Owens, Sami, and Fargeon (2006). Results suggest young women in the ADHD group (n = 107), when compared to the comparison group of young women of matched age and ethnicity (n = 73), had lower achievement test scores; showed higher incidences of grade failures, suspensions, and expulsions; received fewer school-based honors and awards; and used school special services in greater numbers. Effect sizes between the ADHD and comparison groups ranged from medium to large. All group differences withstood control of demographic, cognitive, and comorbidity- related covariates. Contrary to prediction, the students with ADHD had graduated from high school and enrolled in some form of postsecondary education in numbers similar to their peers without the disorder. However, the students with the disorder showed a greater tendency to enroll in community colleges or trade schools rather than four- year colleges or universities and demonstrated a pattern of dropout following postsecondary institution enrollment different from that of their peers without the disorder. Overall, this investigation provides strong evidence for the association between ADHD in girls and a long-term outcome of impairment in the educational domain in adolescence and early adulthood, as has been found in parallel research using largely male samples.